Pembiasaan Membaca Ratibul Haddad Sebagai Sarana Pembentukan Karakter Religius Santri Di Pondok Pesantren Al - Falah Jatilawang Banyumas - Wahyuni Khasanah, Fadliyah; Hizbul Muflihin, M. Hizbul (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Religious character education has become an urgent necessity amid the widespread moral degradation among the younger generation, including santri who are expected to serve as role models in morals and spirituality. Islamic boarding schools (pondok pesantren) play a significant role in shaping this character through systematic and continuous religious activities. The main issue in this study is how the habituation of reading Rātibul Haddād contributes to the formation of the religious character of students at Pondok Pesantren Al-Falah Jatilawang, Banyumas. The aim of this research is to describe the process of religious character formation among santri through the regular practice of reading Rātibul Haddād within the pesantren environment. This study employs a descriptive qualitative approach with data collection techniques including participatory observation, in-depth interviews with caregivers, teachers, and santri, as well as documentation of activities. The research was conducted at Pondok Pesantren Al-Falah Jatilawang, Banyumas, focusing on students who consistently participate in the reading of Rātibul Haddād . The data were analyzed using the stages of compiling, disassembling, reassembling, interpreting, and concluding. The results show that the formation of students’ religious character through the reading of Rātibul Haddād involves five main stages: (1) preparation for the recitation activity, (2) implementation of the recitation in both collective (jama‘ah) and individual settings, (3) habituation and religious character formation, (4) monitoring and evaluation of student behavior by caregivers and teachers, and (5) identifying and addressing obstacles such as a lack of focus or motivation among some students